Come to Church: you will receive blessings Contrasting Prosperity Gospel Teachings with Justification by Faith Alone when Proclaiming the Good News - Mudau, Ndidzulafhi (Missionalia, 2025)
The prosperity gospel movement has achieved considerable prominence in modern Christianity, especially in developing areas, offering material wealth and physical well-being to churchgoers who exhibit adequate faith. This theological perspective opposes the Reformation idea of justification by faith alone, highlighting salvation as a divine gift attained by faith rather than human endeavour or monetary transaction. This study investigates the theological conflicts between prosperity gospel teachings and the notion of justification by faith alone, evaluating their differing interpretations of blessing, salvation, and the Christian existence. The study is positioned within the worldwide framework of contemporary Christianity, focussing specifically on areas where prosperity theology has thrived in conjunction with conventional evangelical doctrines. A thorough literary analysis methodology is utilised, scrutinising core theological texts, biblical exegesis, historical church records, and modern scholarly critiques to assess both theological perspectives. The results indicate major theological discrepancies between prosperity gospel doctrines and the principle of justification by faith alone. The prosperity gospel advocates for worldly affluence as a sign of divine favour, whereas justification by faith underscores spiritual development irrespective of monetary conditions. The research indicates that prosperity teachings frequently result in spiritual disillusionment when anticipated advantages do not manifest, whereas justification by faith offers a more robust foundation for faith in the face of suffering. Justification by faith alone provides a theologically sound alternative to prosperity gospel doctrines, anchoring Christian identity in divine grace rather than material success. This conventional theory offers pastoral alternatives for confronting sorrow and disappointment that prosperity theology fails to address enough. This research enhances modern theological dialogue by demonstrating that justification by faith alone counters the excesses of the prosperity gospel, while providing constructive approaches for pastoral care, biblical interpretation, and spiritual formation across many Christian contexts.